Nanocellulose as Reinforcement in Carboxymethylcellulose Superabsorbent Nanocomposite Hydrogels - Lima, Giovanni F.; Souza, Alana G.; Rosa, Derval dos S. (Macromolecular symposia., 2020)
Carboxymethylcellulose (CMC) is an abundant and low‐cost material that can be used to synthesize environmentally friendly superabsorbent hydrogels for numerous applications. However, this biopolymer results in hydrogels with poor mechanical properties; different fillers can be used to improve this property, but occasionally can decrease the swelling capacity. Nanocelluloses (NC) are an excellent option to improve hydrogel physicochemical characteristics. In this work, CMC‐hydrogels are prepared using citric acid, and NC is added as a filler in different contents: 1, 3, and 5 wt%. The Fourier Transformed Infrared spectroscopy (FTIR) is used to confirm the crosslink reaction, and a peak related to the carboxylic acid functional group confirmed the hydrogel formation. The NC incorporation didn't change the FTIR spectrum since both materials have a similar structure. The water absorption analysis indicated that the developed can be classified as superabsorbent since all of them show an absorption capacity above 40 g.g−1. Besides that, NC played an essential role in the water absorption capacity, the incorporation of 3% of NC resulted in a material with a degree of swelling of, approximately 100 g.g−1. The NCs act as an excellent filler, improving the storage modulus significantly, i.e., the mechanical resistance of the material. The developed hydrogels showed exceptional characteristics, being adequate to various applications, mainly agricultural ones aiming for the water delivery to the soil.